Democratic Transition or Autocratic Adjustment? Constitutional Amendments in Kazakhstan and Uzbekistan in 2022–2023 - Czachor, Rafał (Review of European and Comparative Law, 2024)
Central Asian states have recently implemented significant constitutional reforms. In the case of the authoritarian republics of Kazakhstan and Uzbekistan, the nature of the constitutional amendments, introduced in 2022 and 2023, respectively, is hard to accurately assess. On the one hand, they are a step towards democratization and strengthened guarantees of human rights and freedoms; on the other, they reinforce the current undemocratic government mechanisms. This article discusses the most recent constitutional reforms in both countries, distinguishing three main areas of change: ideology, social issues, and governance mechanisms. It is argued that these reforms generally fall within the paradigm of authoritarian constitutionalism and are an adjustment of the countries’ constitutions to the current needs of their undemocratic presidents.